2020
DOI: 10.1002/acr.23996
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapists’ Falls Prevention Knowledge, Beliefs, and Practices in Osteoarthritis Care: A National Cross‐Sectional Study

Abstract: Objective: To investigate physiotherapists' knowledge, beliefs and current practice around falls prevention in osteoarthritis (OA) care.Methods: Currently registered, practicing Australian physiotherapists who care for people with hip and/or knee OA were invited to participate in this cross-sectional study. A comprehensive online survey was used to collect data that were analysed descriptively or using chi-square tests; free-text responses were classified into key themes for analysis.Results: Complete response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
5
9
0
Order By: Relevance
“…Heng et al [ 44 ] reported inconsistencies in falls education, content and delivery which limited the ability of patients to understand their risk of falling during an admission. Time constraints and lack of staffing capacity and resources were other challenges, in agreement with Ackerman et al [ 45 ], Keyworth et al [ 43 ] and Svavarsdóttir et al [ 25 ]. There was often over-reliance on processes and forms which can take the focus away from clinical judgement [ 46 ].…”
Section: Discussionsupporting
confidence: 74%
“…Heng et al [ 44 ] reported inconsistencies in falls education, content and delivery which limited the ability of patients to understand their risk of falling during an admission. Time constraints and lack of staffing capacity and resources were other challenges, in agreement with Ackerman et al [ 45 ], Keyworth et al [ 43 ] and Svavarsdóttir et al [ 25 ]. There was often over-reliance on processes and forms which can take the focus away from clinical judgement [ 46 ].…”
Section: Discussionsupporting
confidence: 74%
“…Among 370 Australian PTs who work with patients with hip and knee osteoarthritis, discrepancies were noted in the therapists' knowledge of fall prevention and use of appropriate tools to screen for fall risk. Although 84% of the PTs reported having fall-related education, 61% reportedly did not use fall-risk screening tools [10]. The PTs who reported using screening tools used a wide variety of tools.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the uptake of the evidence-based practice approach has been inconsistent within physiotherapy (Scurlock-Evans et al, 2014). Ackerman et al (2020) reported than Australian physiotherapists would not always take evidence-informed approaches when conducting falls risk assessment and falls prevention to patients with osteoarthritis (Ackerman et al, 2020). Such aspects could be further explored among Portugal and UK-based physiotherapists.…”
Section: Discussionmentioning
confidence: 99%